Способ получения газопоглотителя из порошка титана - Ильин А. П. Александр Петрович; Коршунов А. В. Андрей Владимирович; Толбанова Л. О. Людмила Олеговна; Мостовщиков А. В. Андрей Владимирович
опубл. 20.07.11